2019
DOI: 10.2147/idr.s191892
|View full text |Cite
|
Sign up to set email alerts
|

<p>High prevalence of KPC-2-producing hypervirulent&nbsp;<em>Klebsiella pneumoniae</em>&nbsp;causing meningitis in Eastern China</p>

Abstract: BackgroundKlebsiella pneumoniae has been the leading causative pathogen for adult bacterial meningitis in several Asian countries. The clinical and microbiological characteristics of K. pneumoniae meningitis in mainland China are still unknown.Materials and methodsThe clinical data of patients with K. pneumoniae meningitis from January 2011 to July 2017 in a tertiary hospital were retrospectively evaluated. The isolates were tested for antibiotic-resistance genes, virulence-associated genes, and molecular subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 34 publications
8
69
0
1
Order By: Relevance
“…Second, although we identified 19 fecal ST11-CR-HvKP colonization isolates, none of the colonized patients had ST11-CR-HvKP infections. A previous investigation described the high prevalence and mortality rate of ST11-CR-HvKP meningitis in our hospital [8], and K64 was also the most common serotype detected in this study. Future investigations addressing the transition from ST11-CR-HvKP carriage to infection in high-risk patients will be of great significance.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Second, although we identified 19 fecal ST11-CR-HvKP colonization isolates, none of the colonized patients had ST11-CR-HvKP infections. A previous investigation described the high prevalence and mortality rate of ST11-CR-HvKP meningitis in our hospital [8], and K64 was also the most common serotype detected in this study. Future investigations addressing the transition from ST11-CR-HvKP carriage to infection in high-risk patients will be of great significance.…”
Section: Discussionsupporting
confidence: 74%
“…The identification of this ST11-CR-HvKP strain demonstrated that carbapenem resistance and virulence had converged in an epidemic clone that could become a serious public health issue [5]. Subsequently, cases of ST11-CR-HvKP infection have been documented in diverse regions in China [6][7][8]. These reports suggest that this clone is widely spread in China; however, the underlying mechanism that enables its wide dissemination remains unclear.…”
Section: Introductionmentioning
confidence: 95%
“…24 The emergence of hypervirulent lineages carrying antimicrobial resistance genes including carbapenemases is now being increasingly reported: with limited treatment measures and high mortality, they are considered a "super-bug". [18][19][20][21] With reports of hypervirulent CRKP increasing rapidly in China, [25][26][27][28][29] we sought to deep dive into the details of this emergence using microbiological characterization and patient metadata acquired in a single large hospital in Wenzhou, China from 2003 to 2016. In this study, we identified the resistance mechanism and virulence characteristics of 214 isolates of CRKP from amongst 2299 total isolates of K. pneumoniae associated with infection, and the proportion of isolated CRKP was increasing and reaches up to 20% in the final year of the study (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we showed that previous neurosurgery within 4 weeks could help clinicians to identify patients of high risk to acquire pVir + -KPC-kp infections (p = 0.002). Our previous study reported that about half of K. pneumoniae meningitis was caused by pVir + -KPC-kp in our hospital from 2011 to 2017 [27]. In order to establish the correlation of neurosurgery and meningitis, we performed subgroup analysis of post-neurosurgery patients.…”
Section: Discussionmentioning
confidence: 99%